Multilevel Evaluation of Rapid Weight Loss in Wrestling and Taekwondo - Castor-Praga, Cecilia; Lopez-Walle, Jeanette M.; Sanchez-Lopez, Javier (Frontiers in Sociology, 2021)
The practice of strategies for rapid weight loss (RWL) involve diverse factors, such as individual expectations, social interactions, structural elements, etc., conforming to a “culture” of RWL, which must be evaluated and understood in a broad sense. Based on the need of a comprehensive evaluation of the use of RWL in practitioners of combat sports, an ad hoc questionnaire designed for this study, which includes the types and detailed descriptions of RWL strategies, that athletes currently use, the prevalence and frequency of use, the physiological and psychological consequences, the perception of the effect of RWL on their own performance and finally, the individuals who influence the adoption of this practice. One hundred and sixty combat athletes from wrestling and taekwondo disciplines, from Mexico, filled out this questionnaire. Data collected for their statistical analyses. Results revealed a RWL strategies prevalence of 96% across the participants. Our results revealed that 57% of those athletes using RWL lose more than 5% of their body mass. Across the athletes, the most commonly used RWL strategies and with higher intensity were increased exercise and training with plastic or thick clothes. The greater the relative weight loss, the greater the presence of physiological symptoms in athletes, such as rapid breathing and blood pressure. Athletes also mentioned mood states such as tiredness, sadness, confusion, fatigue and vigor, these last two positive and negative mood states are associated with the relative weight loss, respectively. Finally, the people who most influenced the adoption of RWL strategies were the coaches, parents and nutritionists. In conclusion, the questionnaire prepared for this study allowed us to obtain valuable information about the several factors, and their interactions, involved in the practice of RWL in combat athletes. This type of practice could increase health risks and decrease their performance. Therefore, here we state the importance of a comprehensive evaluation of RWL strategies that allows the development of psycho-educational and social-based interventions and programs for the promotion of proper weight maintenance, and prevention against RWL strategies, involving the individuals who influence the adoption of these practices and supporting it with the help of communication technologies.